The various facets of a message: an analysis of the thematic structure in Bridget Jones's Diary in the light of the systemic functional grammar, corpus linguistics and translation studies interface - Paquilin, Viviane (2005)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.